Bioefficacy of gamma radiation on Spodoptera littoralis (Lepidoptera: Noctuidae). Issue 2 (3rd April 2022) - Housam Abd El-Monem Ahmed, Dina
ABSTRACT: The application of nuclear techniques to control one of the most important lepidopteran insect pests: the Egyptian cotton leafworm, Spodoptera littoralis is discussed in this study. All experiments had the objective of finding the dose of gamma radiation capable of causing sterility in the first generations by irradiating the parental generation. For S. littoralis, 6 th instar larvae were irradiated with doses of 40, 80, 120 and 160 Gy. The larval survival was 93%, 90%, 88%, 85% and 97% at 40, 80, 120, 160 and 0 Gy, respectively. The pupal survival was 88, 85, 83, 80 and 98% at the same doses. Hence, there was a reduction in survival and emergence to the adult stage after treating S. littoralis larvae with radiation. Also, the latent effects of the tested gamma doses on 6 th instar larvae of S. littoralis are recorded. The total number of eggs/female and egg fertility were significantly reduced as compared to control, these effects were increased with increasing the dose. It is concluded that radiation is a promising control method for S. littoralis and other related lepidopteran species.